Contribution of Haptic Simulation to Analogic Training Environment in Restorative Dentistry. Issue 3 (16th March 2020) - Vincent, Marin; Joseph, David; Amory, Christophe; Paoli, Nathalie; Ambrosini, Pascal; Mortier, Éric; Tran, Nguyen
Abstract: The aim of this study was to evaluate the contribution of virtual reality to the conventional analogic training environment and show the complementarity of conventional techniques and virtual reality in the learning of dental students. All 88 first‐year dental students at a dental school in France in early 2019 were randomly assigned to one of two groups: group 1 (n = 45) was assigned to cavity preparations on a haptic simulator (Virteasy) and group 2 (n = 43) was assigned to conventional practical work on plastic analogue teeth (Kavo). Following three training sessions, the students in group 1 took a final exam on the same plastic analogue teeth exercise. The results showed improvement in the drilling skill of both groups. The simulator‐trained group (group 1) had similar results to the plastic analogue‐trained group (group 2) in the final test on a plastic analogue tooth. In this study, virtual reality allowed an assessment based on objective criteria and reduced the subjectivity of evaluations conducted on plastic analogue teeth. Considering the saving of supervision and teaching time as well as the material gain offered by virtual reality, the learning methods of haptic simulators are educational options that should be considered by dental educators.